A nutrient mixture inhibits glioblastoma xenograft U-87 MG growth in male nude mice - Roomi, M.W.; Kalinovsky, T.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2016)
Background: Brain tumors are highly aggressive tumors characterized by secretions of high levels of matrix metalloproteinase-2 and -9, leading to tumor growth, invasion and metastasis by digesting the basement membrane and extracellular matrix components. We previously demonstrated the effectiveness of a nutrient mixture (NM) containing ascorbic acid, lysine, proline, and green tea extract in vitro: on activity of urokinase plasminogen activator, matrix metalloproteinases and TIMPs in various human glioblastoma (LN-18, T-98G and A-172) cell lines and on glioblastoma A-172 cell proliferation and Matrigel invasion. Aim: Our main objective in this study was to investigate the effect of the NM in vivo on human glioblastoma U-87 MG cell line. Materials and Methods: Athymic male nude mice inoculated with 3·106 U-87 MG cells subcutaneously and were fed a regular diet or a regular diet supplemented with 0.5% NM. Four weeks later, the mice were sacrificed, the tumors were weighed and measured. The samples were studied histologically. Results: NM inhibited tumor weight and tumor burden by 53% (p = 0.015) and 48% (p = 0.010), respectively. Conclusions: These results suggest the therapeutic potential of NM as an adjuvant in the treatment of glioblastoma.